Long-Term Follow-Up of the Auditory Threshold After a Fully Implantable Middle Ear Implant - Monini, Simonetta; Filippi, Chiara; Salerno, Gerardo; Barbara, Maurizio (Frontiers in Neurology, 2022)
A fully implantable active middle ear device has been proposed and indicated for the rehabilitation of bilateral moderate or moderate-to-severe sensorineural hearing loss, assuming it would overcome the disadvantages of a conventional hearing aid. The indications have further been extended to severe or severe-to-profound forms of hearing loss in the case of an expected limited or null efficacy of hearing aids. While the literature has highlighted several positive aspects of the device, including a better quality of life related to its invisibility, the improvement of auditory and perceptual functions has not been controlled for throughout a long period of follow-up. The present study aimed to verify the behavior of the auditory threshold, especially the bone conduction (BC) component, in the implanted ear in a group of implantees affected by initial bilateral symmetric hearing loss of different severity grades. The BC threshold was assessed preoperatively at activation and at the last follow-up (ranging from 4 to 12 years) in the implanted ear, and preoperatively and at the last follow-up in the contralateral ear, to monitor eventual deteriorated values in both ears over time. The pure tone average (PTA; 250–4,000 Hz), speech reception threshold (SRT) and the maximum word recognition score as a percentage (% WRS) and in dB HL were measured in the implanted ear to verify the efficacy of the device after the first fitting at device activation. A significant worsening of the BC threshold with respect to the baseline threshold was noticed during further follow-up. When comparing the implanted ear with the contralateral ear, a significant worsening of the bone PTA was assessed in the former with respect to the contralateral ear. Despite the worsened hearing found in the implanted ears, the beneficial gains in PTA and speech audiometry observed at the first activation remained constant at the follow-up, thus showing an extension of the efficacy of this device in aiding those with up to the most severe forms of sensorineural hearing loss.